ANALYSIS OF THE PATH TO TOURISM SERVICE INNOVATION IN UZBEKISTAN BASED ON DIGITAL TECHNOLOGY - zhu, yuming (THE INNOVATION ECONOMY, 2026)
This study explores how digital technology promotes tourism service innovation in Uzbekistan in the context of the Belt and Road Initiative. This study constructs a comprehensive analysis framework that integrates Michael Porter’s value chain model and service value chain theory, and systematically analyzes the current situation and pain points of Uzbekistan’s tourism industry from the four dimensions of "people, things, space, and supply". This study finds that despite facing budget constraints and insufficient infrastructure, Uzbekistan’s tourism service industry can still try a variety of unique innovation paths.